Integrated transcriptomic and pathway analyses of sorghum plants revealed the molecular mechanisms of host defense against aphids - Shrestha, Kumar; Huang, Jian; Yan, Liuling; Doust, Andrew N.; Huang, Yinghua (Frontiers in Plant Science, 2024)
Sugarcane aphid has emerged as a major pest of sorghum recently and a few sorghum accessions were identified for resistance to this aphid so far. However, the molecular and genetic mechanisms underlying this resistance are still unclear. To understand these mechanisms, transcriptomics was conducted in resistant Tx2783 and susceptible BTx623 sorghum genotypes infested with sugarcane aphids. A principal component analysis revealed differences in the transcriptomic profiles of the two genotypes. The pathway analysis of the differentially expressed genes (DEGs) indicated the upregulation of a set of genes related to signal perception (nucleotide-binding, leucine-rich repeat proteins (NLR)), signal transduction (mitogen-activated protein kinases (MAPK) signaling, salicylic acid (SA) and jasmonic acid (JA)) and plant defense (transcription factors, flavonoids and terpenoids). The upregulation of the selected DEGs was verified by RT-qPCR data analysis, performed on the resistant and susceptible genotypes. A phytohormone bioassay experiment showed a decrease in aphid population, plant mortality and damage in the susceptible genotype when treated with JA and SA. Together, the results indicate that the set of genes, pathways and defense compounds are involved in host plant resistance to aphids. These findings shed light on the specific role of each DEG; thus, advancing our understanding of the genetic and molecular mechanisms of host plant resistance to aphids.